2007
DOI: 10.1002/joc.1568
|View full text |Cite
|
Sign up to set email alerts
|

The variation of discharge entering the Niger Delta system, 1951–2000, and estimates of change under global warming

Abstract: A simple and effective statistical scheme for estimating river discharges on the River Niger has been derived using catchment rainfall data. Observed station annual average discharges at two locations were correlated with averaged annual rainfall data in recent years . A comparison of the estimated discharge and the observed discharge showed good agreement. The upstream station of Gaya on the border of Niger and Nigeria, with more extensive records, was used to validate the technique. A more limited discharge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…PAETH et al 2007 was not extreme in terms of the daily rain events but of 5-day up to 20-day accumulated rainfall totals. This is consistent with the physical idea of large-scale flooding along the main streams in sub-Saharan Africa which is not triggered by individual rain events but by a sequence of heavy rainfall over several days or even weeks (Todd and Washington, 2004;Itiveh and Bigg, 2008). The timing of the heavy precipitation period is indicated in the bottom right panel of Figure 5: counting from the 1st of June 2007 extreme rain events first took place in June and July over Central and Eastern Africa, as well as along the Guinean Coast, in August over the Western Sahel Zone with maximum over Burkina Faso, and in September over Southern Algeria.…”
supporting
confidence: 88%
See 2 more Smart Citations
“…PAETH et al 2007 was not extreme in terms of the daily rain events but of 5-day up to 20-day accumulated rainfall totals. This is consistent with the physical idea of large-scale flooding along the main streams in sub-Saharan Africa which is not triggered by individual rain events but by a sequence of heavy rainfall over several days or even weeks (Todd and Washington, 2004;Itiveh and Bigg, 2008). The timing of the heavy precipitation period is indicated in the bottom right panel of Figure 5: counting from the 1st of June 2007 extreme rain events first took place in June and July over Central and Eastern Africa, as well as along the Guinean Coast, in August over the Western Sahel Zone with maximum over Burkina Faso, and in September over Southern Algeria.…”
supporting
confidence: 88%
“…From eye-witness reports it was concluded that the 2007 flooding was the worst for a generation. Apparently, the negative implications were enhanced by the fact that the rainy season started later than normal in Western Africa (Levinson and Lawrimore, 2008;NIMET, 2008) such that heavy rainfall fell on dry soils, leading to stronger surface runoff and flooding along rivers, in particular, the Niger and Volta Rivers (Itiveh and Bigg, 2008). While the majority of the media reports tended to draw a dramatic picture of the 2007 flood in Africa, others criticized that the spatio-temporal extent and intensity of the flood were exaggerated in order to draw the attention of potential donors to Africa (Goldman Morgenstern and Partners, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that Itiveh and Bigg [50], using only field data, noticed at the entry of the Niger delta system in Nigeria, -a strong relationship between precipitation and the discharge data from both sections of the Niger River basin‖, without introducing the effects of either land cover or land use change. But conclusions corroborate some modeling based previous works: Li et al [51] [53] highlighted the role of the -reduction in the baseflow related to the cumulated rainfall deficit‖.…”
Section: Discussionmentioning
confidence: 99%
“…Based on observed data in the downstream reach of Niger River (at the entry of the Niger River Delta), a study by Itiveh and Bigg [62] highlighted a high correlation between precipitations on the whole Niger basin and discharge, without introducing any effect of land cover change. Their observations contradicted previous results obtained by modelling, such as those of Li et al [63], which analyzed whether LULCC affected hydrological regimes at the basin scale for the Niger River and Lake Chad basins, and found that a total deforestation would lead to an increase in runoff coefficient from 0.15 to 0.44.…”
Section: Guinean Rivers Have the Same Behaviormentioning
confidence: 99%